Herpetic Whitlow: A Case Complicated with Candidemia - Canan Özlü; Hatice Karaoğlu Asrak; Nurşen Belet (Trends in Pediatrics)
Herpetic whitlow is a herpes simplex virus infection of fingers affecting the distal phalanx. The disease is often misdiagnosed as a bacterial infection which leads to inappropriate treatments. In this paper, we reported a case of herpetic whitlow in a 10-month-old girl who is misdiagnosed as bacterial paronychia and treated with surgical intervention and broad-spectrum antibiotics, as a result, she had invasive candidiasis which has a high mortality rate. Physicians should be aware of this entity for correct initial diagnosis and accurate management.